Comparing statistical learning across perceptual modalities in infancy: An investigation of underlying learning mechanism(s). Issue 6 (2nd July 2019) - Emberson, Lauren L.; Misyak, Jennifer B.; Schwade, Jennifer A.; Christiansen, Morten H.; Goldstein, Michael H.
Abstract: Statistical learning (SL), sensitivity to probabilistic regularities in sensory input, has been widely implicated in cognitive and perceptual development. Little is known, however, about the underlying mechanisms of SL and whether they undergo developmental change. One way to approach these questions is to compare SL across perceptual modalities. While a decade of research has compared auditory and visual SL in adults, we present the first direct comparison of visual and auditory SL in infants (8–10 months). Learning was evidenced in both perceptual modalities but with opposite directions of preference: Infants in the auditory condition displayed a novelty preference, while infants in the visual condition showed a familiarity preference. Interpreting these results within the Hunter and Ames model (1988), where familiarity preferences reflect a weaker stage of encoding than novelty preferences, we conclude that there is weaker learning in the visual modality than the auditory modality for this age. In addition, we found evidence of different developmental trajectories across modalities: Auditory SL increased while visual SL did not change for this age range. The results suggest that SL is not an abstract, amodal ability; for the types of stimuli and statistics tested, we find that auditory SL precedes the development of visual SL and is consistent with recent work comparing SL across modalities in older children. Abstract : This paper presents the first direct comparison of statistical learning across auditory and visual modalities in infants. Despite finding robust evidence of learning, statistical learning was not identical across modalities indicating that it is not an abstract, amodal ability even in infancy.